Replication-Independent Histone Deposition by the HIR Complex and Asf1 - Green, Erin; Antczak, Andrew J.; Bailey, Aaron O.; Franco, Alexa A.; Wu, Kevin J.; 3rd, John R. Yates; Kaufman, Paul D. (Cell Press, 2005)
The orderly deposition of histones onto DNA is mediated by conserved assembly complexes, including Chromatin Assembly Factor-1 (CAF-1) and the Hir proteins [1–4]. CAF-1 and the Hir proteins operate in distinct but functionally overlapping histone deposition pathways in vivo [5, 6]. The Hir proteins and CAF-1 share a common partner, the highly conserved histone H3/H4-binding protein Asf1, which binds the middle subunit of CAF-1 as well as to Hir proteins [7–11]. Asf1 binds to newly synthesized histones H3/H4 [12] and this complex stimulates histone deposition by CAF-1 [7, 12, 13]. In yeast, Asf1 is required for the contribution of the Hir proteins to gene silencing [7, 14]. Here, we demonstrate that Hir1, Hir2, Hir3 and Hpc2 comprise the HIR complex, which co-purifies with histone deposition protein Asf1. Together, the HIR complex and Asf1 deposit histones onto DNA in a replication-independent manner. Histone deposition by the HIR complex and Asf1 is impaired by a mutation in Asf1 that inhibits HIR binding. These data indicate that the HIR complex and Asf1 proteins function together as a conserved eukaryotic pathway for histone replacement throughout the cell cycle.